A randomized controlled trial comparing early versus late oral feeding after cesarean section under regional anesthesia - Mawson AL; Bumrungphuet S; Manonai J (Dove Medical Press, 2019)
Apinun Luksanachinda Mawson, Sommart Bumrungphuet, Jittima Manonai Department of Obstetrics and Gynecology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Sommart BumrungphuetDepartment of Obstetrics and Gynecology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok 10400, ThailandTel +66 2 201 1412Email sommart.bum@mahidol.ac.thObjective: To compare the return of bowel movements in regionally anesthetized women undergoing cesarean section (C-section) given Early Oral Feeding (EOF) to that of women given Late Oral Feeding (LOF). Secondary outcomes of maternal satisfaction and gastrointestinal complications were also examined.Methods: In a single-blinded randomized controlled trial (TCTR20181202001), 148 singleton pregnant women undergoing elective C-sections with regional anesthesia were assigned to receive either EOF or LOF. Participants began to sip water at 6–8 hrs or more than 12 hrs post-operation, for EOF or LOF respectively. Participants were then placed onto a stepping diet as tolerated. Participants failing to tolerate the stepping diet or those having surgical complications were excluded from the study.Results: After exclusion, 69 women remained in the EOF group and 67 in the LOF group. The ages of participants ranged from 19 to 42, with a mean of 32.07. There was no-loss follow up and no significant difference in patient characteristics, except the site of the surgical incision. Participants given EOF were more likely to experience bowel sound the next morning than patients given LOF (EOF 87.0%, LOF 44.8%, P-value<0.001). However, there was no difference in time to passing flatus and time to passing stool. Maternal satisfaction regarding hunger (EOF 3.78±0.91, LOF 3.24±1.01, P-value 0.002) and maternal satisfaction with postoperative consumption (EOF 4.38±0.64, LOF 4.13±0.48, P-value 0.049) were significantly higher in the EOF group. There was no difference in gastrointestinal complications between the groups (P-value 0.978).Conclusion: The EOF group experienced an earlier return of bowel movement and greater maternal satisfaction than the LOF group, with no difference in gastrointestinal complications. These findings support the recommendation of EOF for women who undergo uncomplicated C-sections under regional anesthesia.Keywords: early oral feeding, cesarean section, maternal satisfaction, bowel function, gastrointestinal complication, randomized controlled trial